A Study on the Correlation between SLC25A26 Polymorphism and Gastritis and Gastric Ulcers in Koreans - Soyeun PARK; Dahyun HWANG (Korean Journal of Clinical Laboratory Science, 2023)
Gastritis is an inflammation of the gastric mucosa and gastric ulcers are a break in the mucosa of the stomach lining. Past research on gastritis and gastric ulcers has been mainly conducted from the perspective that environmental factors are the primary cause of these gastric diseases. However, recently the importance of genetic factors has been emphasized due to current developments in genetic research. The SLC25A26 gene is believed to be associated with the accumulation of reactive oxygen species. Oxidative stress promotes an inflammatory response, which increases the production of free radicals and causes cellular damage, and these lead to the development of gastric diseases. In this study, the correlation between SLC25A26 and gastric diseases was analyzed. Polymorphisms in SLC25A26 were analyzed in 1,369 domestic gastric disease patients and 7,471 healthy controls. As a result, 11 single nucleotide polymorphisms (SNPs) (in the genotype) and 13 SNPs (in the imputation) showed statistical significance (P＜0.05), and high relative risk of gastric diseases. Among them, the rs13874 allele of SLC25A26 showed a highly significant association with gastric diseases. In the genotype-based mRNA expression analysis, the minor allele (C) group showed increased mRNA expression and this could increase oxidative stress. In conclusion, SLC25A26 polymorphisms are associated with gastric diseases. These results may provide a basis for new guidelines for gastric disease management in the Korean population.